Knowledge, attitude, and practice toward COVID-19 among nurses - Murtaza, Ghulam; Badil; Raja, Raja; Gulsher, Gulsher; Khan , Kashif Khan; Khan , Ameer Ullah Khan (Journal of University Medical & Dental College, 2023)
ABSTRACT BACKGROUND & OBJECTIVE: COVID-19 is caused by the SARS-CoV-2 virus. It can lead to mild to severe respiratory illness, as well as death. Nurses are frontline health workers to care the COVID-19 patients effectively. The objective of the study was to determine the knowledge, attitude, and practice regarding COVID-19 among nurses working at tertiary care public sector hospitals in Karachi. METHODOLOGY: Analytical cross-sectional study was conducted at Shaheed Mohtarma Benazir Bhutto Institute of Trauma, Karachi, for three months from October to December 2020. The calculated sample size was 239 nurses of both genders. Non-probability convenient sampling technique was used to access the participants. A validated and open accessed tool was used for data collection. A Chi-square test was used to assess the association of Knowledge, attitude, and practice toward COVID-19 with demographic variables. The level of significance was considered with a p-value ≤0.05. RESULTS: Out of the total, 145 (59.4%) were female, and a majority of 158 (66.1%) of the study subject’s ages ranged from 25-30 years old. Mostly 156 (65.3%) of the study participants had a diploma in nursing. Approximately half of 130 (54.4%) of the participants worked the morning shift. The majority of 209 (87.4%) participants’ experiences were two years and above. The gender and work experience of the participants were found statistically significant (p-value<0.05). This also found that more experienced nurses were somewhat better to mean Knowledge (7.87) than less experienced nurses (7.13). CONCLUSION: It is concluded that most of the study participants had sound Knowledge, a positive attitude towards its remedy, and appropriate practice towards COVID-19. KEYWORDS: COVID-19, Nurses, Knowledge, Attitude, Practice